Purification, characterization, and lytic activity against Naegleria fowleri of two amoebicins produced by Bacillus licheniformis A12. - Gálvez, A (1993)
Bacillus licheniformis A12 produces two amoebolytic substances (amoebicins A12-A and A12-B) in liquid media during sporulation. Both substances have been purified and characterized. They are heat- and protease-resistant peptides containing aspartic acid, glutamic acid, serine, proline, and tyrosine in a molar ratio of 5:2:2:2:2. No fatty acids or carbohydrates have been detected. Their molecular weight is 1,430. Purified amoebicins A12-A and A12-B exhibit amoebolytic action against Naegleria fowleri. They also exhibit antibiotic action against yeasts (Saccharomyces heterogenicus and Cryptococcus neoformans) and several fungal species (Aspergillus niger, Microsporum canis, Mucor plumbeus, and Trychophyton mentagrophytes). Their antibacterial spectrum appears to be restricted to Bacillus megaterium, Corynebacterium glutamicum, and Sarcina sp.